Identyfikacja Układów Mechanicznych o Członach Lepkosprężystych - E. Kamiński (Engineering Transactions, 1973)
The presented paper is related to a former publication [9] by the author. The introduction contains a discussion of the know procedures of general and complete identification, in the cases of deterministic and random excitation; next, a new variant of identification is presented, based on the principle of separation of principal vibration modes. This method enables us to determine the values of coefficients of the equations of motion of the object, also in the case when it contains viscoelastic elements.